2013
DOI: 10.1007/s11357-013-9598-8
|View full text |Cite
|
Sign up to set email alerts
|

In case of obesity, longevity-related mechanisms lead to anti-inflammation

Abstract: The exact mechanisms which contribute to longevity have not been figured out yet. Our aim was to find out a common way for prompting longevity by bringing together the well-known applications such as food restriction, exercise, and probiotic supplementing in an experimental obesity model. Experimental obesity was promoted in a total of 32 young (2 months old) and 32 aged (16 months old) male Wistar albino rats through 8-week cafeteria diet (salami, chocolate, chips, and biscuits). Old and young animals were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…It was found that the IL-1β, which is primed by high-fat diet (HFD) and is cleaved through the NLRP3 inflammasome complex [21,22], and which production in fat tissue is associated with the TLR4 receptor and nuclear factor-κB activation [23,24], directly influences the peripheral insulin resistance and type II diabetes [20,25,21,26,22]. In our study, glucose and insulin levels in blood serum, and HOMA insulin resistance index [16], as well as IL-1β and IL-12Br40 production were also increased in rats with MSG-induced obesity comparing with intact rats.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the IL-1β, which is primed by high-fat diet (HFD) and is cleaved through the NLRP3 inflammasome complex [21,22], and which production in fat tissue is associated with the TLR4 receptor and nuclear factor-κB activation [23,24], directly influences the peripheral insulin resistance and type II diabetes [20,25,21,26,22]. In our study, glucose and insulin levels in blood serum, and HOMA insulin resistance index [16], as well as IL-1β and IL-12Br40 production were also increased in rats with MSG-induced obesity comparing with intact rats.…”
Section: Resultsmentioning
confidence: 99%
“…These disorders are in addition mainly characterised as inflammatory diseases and inflammation is considered a target for therapy (Qian et al 2010;Weksler et al 2009). For example, in a rat obesity model, mainly anti-inflammatory immune responses were positively associated with longevity (Kaya et al 2014) indicating that reduced inflammation could promote healthy ageing.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the rats were fed a HFD that consisted of 60% fat for 10 weeks. After 8 weeks of consuming an obesity-inducing diet, the rats that showed a body weight increase of at least 20% when compared to the control group were regarded as obese [ 44 , 45 ]. The present study found that the rats fed a HFD weighed 40% more than the rats in the control group.…”
Section: Discussionmentioning
confidence: 99%